2014
DOI: 10.1590/s0034-737x2014000200018
|View full text |Cite
|
Sign up to set email alerts
|

Características físico-químicas de cultivares de macieiras pouco exigentes em frio

Abstract: Apple cultivars undemanding as to cold and fruit qualitySouthern Brazil is a traditional apple-growing region. However, new less cold-demanding cultivars are making the cultivation of apples viable in other Brazilian regions, such as in the state of Minas Gerais, where the crop is in a remarkable expansion. The quality attributes of the fruits are important both to the industrialization and the fresh consumption. In this sense, this work was aimed at characterizing fruits of different less-cold demanding apple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Similar results were found by Oliveira et al (2014), who evaluated eight apple cultivars that require short time of cold weather. On the other hand, some studies on mild winter regions showed higher FW means for the cultivar Princesa, differing from the results in the present study (SANTOS et al, 2010;(CHAGAS et al, 2012).…”
Section: Resultssupporting
confidence: 84%
“…Similar results were found by Oliveira et al (2014), who evaluated eight apple cultivars that require short time of cold weather. On the other hand, some studies on mild winter regions showed higher FW means for the cultivar Princesa, differing from the results in the present study (SANTOS et al, 2010;(CHAGAS et al, 2012).…”
Section: Resultssupporting
confidence: 84%